1999
DOI: 10.1016/s0969-2126(99)80174-9
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of human glyoxalase II and its complex with a glutathione thiolester substrate analogue

Abstract: The arrangement of ligands around the zinc ions includes a water molecule, presumably in the form of a hydroxide ion, coordinated to both metal ions. This hydroxide ion is situated 2.9 A from the carbonyl carbon of the substrate in such a position that it could act as the nucleophile during catalysis. The reaction mechanism may also have implications for the action of metallo-beta-lactamases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
316
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(330 citation statements)
references
References 55 publications
13
316
1
Order By: Relevance
“…Based on its similarity to the metallo-␤-lactamases, we predicted that glyoxalase II binds two Zn(II) ions, utilizing five histidines, two aspartic acids, and a bridging water molecule (18). These predictions have been restated by Melino et al (22) and supported through the recent determination of the human glyoxalase II crystal structure (23). The crystallographic data indicates that the metal binding and active sites of glyoxalase II resemble those in the metallo-␤-lactamase L1 from Stenotrophomonas maltophilia (24).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Based on its similarity to the metallo-␤-lactamases, we predicted that glyoxalase II binds two Zn(II) ions, utilizing five histidines, two aspartic acids, and a bridging water molecule (18). These predictions have been restated by Melino et al (22) and supported through the recent determination of the human glyoxalase II crystal structure (23). The crystallographic data indicates that the metal binding and active sites of glyoxalase II resemble those in the metallo-␤-lactamase L1 from Stenotrophomonas maltophilia (24).…”
mentioning
confidence: 73%
“…It could not be purified, and therefore was not analyzed. Lysine 74 is located on the outside of the protein in the middle of a ␤ strand (23). The drastic change in protein solubility likely results from dramatic structural changes.…”
Section: Overexpression and Purification Of Wild Type And Mutantmentioning
confidence: 99%
“…3(B)] was observed. The structures of A. thaliana and human GLX2s as well as other orthologs are composed of two tightly interacting domains: the N-terminal domain, which includes the first 174 residues and has the typical ab/ba fourlayer sandwich metallo-b-lactamase fold 16,17 and the smaller C-terminal domain is situated at one edge of the main core and consists of five helices. This domain is typical of the glyoxalase Type II family and was previously considered to be essential for substrate binding.…”
Section: Crystal Structure Of Ycblmentioning
confidence: 99%
“…This domain is typical of the glyoxalase Type II family and was previously considered to be essential for substrate binding. 16,17 GLX2-5 from A. thaliana mitochondria was crystallized as a dimer held together by a number of electrostatic interactions and with the C-termini buried in the dimeric interface. 18 However, it did not prove possible to confirm dimerization in solution, and thus it was concluded that it must be a crystallization artifact.…”
Section: Crystal Structure Of Ycblmentioning
confidence: 99%
See 1 more Smart Citation